2015
DOI: 10.1063/1.4927054
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and electrical properties of single wall carbon nanotube channel and graphene electrode based transistors arrays

Abstract: A transistor structure composed of an individual single-walled carbon nanotube (SWNT) channel with a graphene electrode was demonstrated. The integrated arrays of transistor devices were prepared by transferring patterned graphene electrode patterns on top of the aligned SWNT along one direction. Both single and multi layer graphene were used for the electrode materials; typical p-type transistor and Schottky diode behavior were observed, respectively. Based on our fabrication method and device performances, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The thickness of a MoS 2 flake was identified via AFM height profiles (Figure b) and micro-Raman spectra (Figure c). A MoS 2 flake with a known thickness could thus be transferred from SiO 2 to Au using a PMMA-mediated transfer technique Figure a shows that a flake could be successfully transferred from one substrate to the other without significantly altering the flake, such that it can be considered to be “identical” before and after the transfer.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of a MoS 2 flake was identified via AFM height profiles (Figure b) and micro-Raman spectra (Figure c). A MoS 2 flake with a known thickness could thus be transferred from SiO 2 to Au using a PMMA-mediated transfer technique Figure a shows that a flake could be successfully transferred from one substrate to the other without significantly altering the flake, such that it can be considered to be “identical” before and after the transfer.…”
Section: Resultsmentioning
confidence: 99%
“…As a member of the carbon allotropes, Graphene has emerged as an alternative electrode material for CNT devices due to its flexibility, exceptional electric transport, and potential for the seamless contact with CNT. While there have been several experimental and theoretical studies on the graphene/SWCNT junction properties, relatively few studies have been reported values of contact resistance in graphene/SWCNT junctions [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…P ercolation is of paramount importance in electrically active nanocarbon composites and hybrid electronic devices where single-walled carbon nanotubes (SWNTs) and graphene enable charge transport across the network. 1,2 Examples of the importance of such percolated networks can be found in flexible electrodes, field-effect transistors, hybrid photovoltaic solar cells, and flexible supercapacitors. 2−5 The minimum amount of interconnected subunits necessary to form a percolated network that enables transport of electricity across the system is called the percolation threshold, ϕ c .…”
mentioning
confidence: 99%
“…Percolation is of paramount importance in electrically active nanocarbon composites and hybrid electronic devices where single-walled carbon nanotubes (SWNTs) and graphene enable charge transport across the network. , Examples of the importance of such percolated networks can be found in flexible electrodes, field-effect transistors, hybrid photovoltaic solar cells, and flexible supercapacitors. The minimum amount of interconnected subunits necessary to form a percolated network that enables transport of electricity across the system is called the percolation threshold, ϕ c . A central question in percolated systems is how to lower ϕ c in order to reduce the amount of materials, to ease processing, and to enhance electrical properties by minimizing bundle formation. , Recently, it was found that reducing the nanotube loading in bulk heterojunction photovoltaic solar cells enabled a decrease in series resistance and an overall enhancement in power conversion efficiency due to better charge transport and extraction . Moreover, a growing number of applications require device miniaturization, formation of nanostructured domains, and the use of highly purified and expensive to produce semiconducting nanotubes to prevent electrical shorts or exciton quenching, e .…”
mentioning
confidence: 99%